Exploring the Items for Measuring the Marketing Information System Construct: An Exploratory Factor Analysis - Shkeer, Amged Saleh; Awang, Zainudin (International Review of Management and Marketing, 2019)
One of the most important factors that affect the decision-making process is the Information system (IS) in any given institution. Accordingly, IS in any institution is closely matching the heart role in a human body. The aim of this research is to perform instrument validation through Exploratory Factor Analysis (EFA). The questionnaire used in this study is adapted from two different studies: Bahloul (2011) and Al-Adamat (2015). It consists of of seven sub-constructs; after the questionnaire was distributed, 100 responses were collected to do the EFA. EFA was done for each construct separately. The results show that all of the seven constructs have one component or dimension, The factor loading for every item in each construct is greater than 0.6, Bartlett’s Test of Sphericity was less than 0.05 for all the constructs, which is Significant (P-value <0.05). Kaiser-Meyer-Olkin Measure of Sampling Adequacy was higher than 0.6 for all the constructs, and this means that the sample size is adequate. Cronbach’s Alpha test was higher than 0.7 for the entire constructs’ items, which means that these items are all reliable. This study found a valid and reliable instrument for measuring the effectiveness of marketing information system components in the decision-making process. Keywords: Exploratory Factor Analysis, Marketing Information System, Decision-Making Process, Information technology JEL Classifications: M31, M30 DOI: https://doi.org/10.32479/irmm.8622